Negotiating illness through faith: Religious narratives of cancer etiology among patients and caregivers in Addis Ababa, Ethiopia - Kaleab Fikre; Abeje Berhanu Kassegne; Getnet Tadele (PLoS ONE, 2026)
Cancer has become a major global public health threat, and individuals diagnosed with cancer and their family caregivers often seek to understand their illness experiences. Religious, spiritual, and sociocultural beliefs play a central role in shaping illness interpretations and care-seeking behaviors. However, in Ethiopia, limited attention has been paid to how these frameworks influence cancer experiences. This study explored religious narratives and interpretations of illness etiology among individuals diagnosed with cancer and their family caregivers and examined their influence on illness experiences and health-seeking practices. An interpretive phenomenological approach was employed using semi-structured, in-depth interviews with 41 participants, including individuals with cancer, family caregivers, and religious leaders. Data were transcribed, translated, and thematically analyzed to examine the processes of meaning-making. The findings showed that participants commonly conceptualized addiction as spiritually mediated rather than merely biologically determined. Illness was frequently interpreted as having a divine or supernatural origin, including punishment, a test of faith, God’s will, or spiritual affliction. These interpretations were dynamic and shaped by religious teachings, sociocultural contexts and personal reflections. Religious frameworks influence emotional responses, coping strategies, and health-seeking behaviors, providing comfort and resilience while shaping treatment decisions. They functioned not only as explanatory frameworks for illness but also as practical resources that structured participants’ responses to and negotiations with uncertainty, suffering, and responsibility. Religious meaning-making plays a central role in illness interpretations and overall experiences in cancer trajectories. Recognizing and engaging with these spiritual frameworks may enhance culturally responsive and patient-centered cancer care. Integrating spiritual sensitivity into clinical practice and collaborating with religious leaders may improve communication, trust, and psychosocial support for patients and their families.